La actividad gremial en Quito (1777-1820): los plateros y batihojas - Paniagua Pérez, Jesús (Estudios humanísticos. Geografía, historia y arte, 1997)
The end of the eighteenth century and begining of the nineteenth delimit a crucial phase in the dismantling of the gilds in Quito. This is particularly true of the silversmiths' guild, the subject of this paper. Internal crises and the first stirrings of the independence movement in the territories covered by the Quito district court had a major effect on developments within the precious-metal workers' organization in this city, wich had been one of the most active sites in Spanish America, with the largest number of craftsmen.